The skin collector - Deaver, Jeffery (New York : Grand Central Publishing, 2014)
Drafted in to investigate a series of killings by a butcher known as the Skin Collector, NYPD detective Lincoln Rhyme and his associate Amelia Sachs have little to go on but a series of cryptic messages left etched into the skin of the deceased.
Keywords: Serial murder investigation -- Fiction; Suspense fiction